Case report: Dementia sensitivity to altitude changes and effective treatment with hyperbaric air and glutathione precursors - Fogarty, Edward F.; Harch, Paul G. (Frontiers in Neurology, 2024)
A 78-year-old man with dementia experienced waxing and waning of symptoms with changes in altitude as he traveled from his home in the Rocky Mountains to lower elevations and back. To replicate the improvement in his symptoms with travel to lower elevations (higher pressure), the patient was treated with a near-identical repressurization in a hyperbaric chamber using compressed air. With four 1-h treatments at 1.3 Atmospheres Absolute (ATA) and concurrent administration of low-dose oral glutathione amino acid precursors, he recovered speech and showed improvement in activities of daily living. Regional broadcast media had documented his novel recovery. Nosocomial COVID-19 and withdrawal of hyperbaric air therapy led to patient demise 7 months after initiation of treatment. It is theorized that hyperbaric air therapy stimulated mitochondrial biochemical and physical changes, which led to clinical improvement.